Analisis Unsur Intrinsik pada Cerpen Sepatu Baru Karya Fitri First Nova Butan Butan (International Forum of Researchers and Lecturers, 2025)
This study aims to examine the intrinsic elements present in a literary work. The analysis of the short story Sepatu Baru by Fitri First Nova Butar Butar includes a discussion of intrinsic elements such as theme, characters, plot, setting, and the message contained within it. This study is categorized as qualitative research using a descriptive method. Data collection techniques are carried out through several steps, including reading, examining, noting, and identifying the content found in the short story. The short story highlights the theme of patience, perseverance, and humility, which can lead to positive outcomes, with settings including the grandmother's house, the classroom, and the teacher's office, the time settings in the morning and afternoon, as well as an atmosphere setting that is comforting and touching.